2017
DOI: 10.1080/0284186x.2017.1304652
|View full text |Cite
|
Sign up to set email alerts
|

Lobectomy for non-small cell lung carcinoma: a nationwide study of short- and long-term survival

Abstract: Introduction: Lobectomy is the standard curative treatment for non-small cell carcinoma (NSCLC) of the lung. Most studies on lobectomy have focused on short-term outcome and 30-day mortality. The aim of this study was to determine both short-term and long-term surgical outcome in all patients who underwent lobectomy for NSCLC in Iceland over a 24-year period. Material and methods: The study involved 489 consecutive patients with NSCLC who underwent lobectomy with curative intent in Iceland, 1991Iceland, -2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…According to data from one cancer center in Estonia, the largest group of LC cases undergoing radical resection was stage IA, but a substantial number of stage IB-III patients were also resected [26]. In Iceland, 15% of patients who underwent lobectomy had stage IIIA disease, which was usually detected postoperatively [27]. Treatment complications and comorbidities have been shown to be important causes of death in early stage LC [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to data from one cancer center in Estonia, the largest group of LC cases undergoing radical resection was stage IA, but a substantial number of stage IB-III patients were also resected [26]. In Iceland, 15% of patients who underwent lobectomy had stage IIIA disease, which was usually detected postoperatively [27]. Treatment complications and comorbidities have been shown to be important causes of death in early stage LC [28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the continuous progress in the technology of cancer diagnosis and treatment, the mortality rate of lung cancer remains high. One reason is that some patients are diagnosed with advanced lung cancer, and the other is that the existing guided staging system is not accurate in predicting the prognosis of lung cancer; as a result, some patients with early lung cancer did not receive adjuvant therapy after operation, which led to the recurrence or metastasis of lung cancer 3,4 . Therefore, it is necessary to update the staging system of the existing guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…VATS is the most common surgery for the thoracic surgery department performed at the day surgery center in recent years 25 . Successful results from a randomized clinical trial were reported in 1994, and lobectomy is considered the gold standard of treatment for NSCLC 26 . However, a number of studies have revealed that lobectomy can substitute sublobar resection for early stage or small peripheral stage I NSCLCs, including wedge resection and segmentectomy, as outcomes are comparable to those after lobectomy 26–28 .…”
Section: Discussionmentioning
confidence: 99%